Environmental entrepreneurialism and the limits and possibilities of socio-economic transformation in the Karoo - Beinart , William; Robins, Steven (New Agenda: SA Journal of Social and Economic Policy, 2025)
In recent decades, a new and multi-crested wave of investment has washed across the Karoo, much of it focused on aspects of what we are calling environmental entrepreneurialism, especially wildlife farming, conservancies, ecotourism, and renewable energy. ‘Sustainable’ copper mining, green hydrogen, and carbon credits are also promised. While driven by the private sector, this has not replaced the state, and it intersects with national and provincial projects that extend protected areas, facilitate conservancies, and regulate renewable energy infrastructure. The latter, with investment largely by private companies on privately-owned land, is probably the most significant area of investment. Renewable energy infrastructure is not directly aimed at benefitting the Karoo environment but at augmenting and decarbonising provincial and national electricity supplies. Other enterprises are similarly complex. While copper mining may enhance global environmental conservation, it is environmentally destructive locally. In this article, we explore some of the dynamics of these environmental trends across different sectors. Generally, they are resulting in national environmental gains and enhancing local biodiversity. However, as we discuss briefly in each case, they are making little impact on socio-economic inequality. Landowners are benefitting and land ownership is increasingly concentrated. New networks of expertise have emerged between farm-owners, government agencies, universities, and private consultancies. We focus primarily on private sector environmental entrepreneurialism as a process of increasing significance and a shift away from the state as the key agent in conservation. Evidence suggests that redistributive processes are marginal, with the partial exception of those resulting from renewable energy licences.